Decentralized Networking Models: Reshaping Digital Architecture - Sasank Tummalpalli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The emergence of decentralized networks represents a fundamental shift in digital infrastructure design and implementation. This comprehensive article explores the evolution of networking architectures from traditional centralized models to modern distributed systems, examining core components, implementation challenges, and future developments. It investigates how decentralized control systems and blockchain technologies are reshaping network topology design, routing protocols, and consensus mechanisms. Through detailed case studies of P2P file sharing, mesh networks, edge computing, and IoT implementations, the article demonstrates the practical applications and benefits of decentralized architectures. It encompasses critical aspects of network performance, including scalability considerations, resilience mechanisms, and resource optimization strategies. Special attention is given to emerging technologies such as AI-enhanced routing solutions, cross-network interoperability, and bio-inspired network designs. The article also addresses security challenges and their solutions in decentralized environments, providing insights into the development of robust and secure network architectures for future applications.